Problems of the Development of the Eurasian Economic Integration: How to Resolve Them? - S. Yu. Glazyev (Евразийская интеграция: экономика, право, политика, 2022)
Aim. Substantiation of the thesis on the need to increase the annual growth of the EAEU economy by 6–8% through the implementation of a unified strategy for the accelerated development of target indicators as the level of economic development converges, their sustainable convergence and the activation of the existing production and scientific and technical potential of the Union Member States. At the same time, the nationally oriented financial policy of the Bank of Russia should play an important role.Tasks. Rationale:– the need to supplement the target development scenario presented in the Guidelines for the Economic Development of the EAEU until 2030 with a strategy for accelerated development and solving national security problems;– formation of a nationwide macroeconomic policy, including its monetary component;– carrying out deoffshorization of the economy and stopping the unauthorized export of capital;– supplementing the Eurasian economic integration with monetary, monetary, educational, scientific and technical policies and the transition to national currencies in mutual trade and investment in the EAEU, CIS, BRICS, SCO.Methods. Macroeconomic modeling, methods of mathematical statistics, big data analysis, demographic analysis.Results. The necessity of a significant refinement of the main directions of the unified state monetary policy of Russia, which ensures its entry into the sixth technological order and the irreversible convergence of the production and scientific and technical potential of the EAEU member states, is substantiated.Conclusion. The proposed comprehensive approach will make it possible to fully implement the adopted Strategic Directions for the Development of Eurasian Economic Integration until 2025, lay the foundations for a new stage of integration with the achievement of significant milestones set in the interests of the countries and peoples of our integration association.